2006
DOI: 10.2337/db06-0337
|View full text |Cite
|
Sign up to set email alerts
|

Bardet-Biedl Syndrome Gene Variants Are Associated With Both Childhood and Adult Common Obesity in French Caucasians

Abstract: Bardet-Biedl syndrome (BBS) is a rare developmental disorder with the cardinal features of abdominal obesity, retinopathy, polydactyly, cognitive impairment, renal and cardiac anomalies, hypertension, and diabetes. BBS is genetically heterogeneous, with nine genes identified to date and evidence for additional loci. In this study, we performed mutation analysis of the coding and conserved regions of BBS1, BBS2, BBS4, and BBS6 in 48 French Caucasian individuals. Among the 36 variants identified, 12 were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 37 publications
3
80
0
3
Order By: Relevance
“…This result for coding variants was replicated in another study in French Caucasians, in which no association was found for four BBS6 coding polymorphisms, including G532V. 12 Furthermore, in the French population two noncoding variants (985 þ 33C4G, À18,597A4T) were found to be significantly more prevalent in obese children compared with control individuals. Children homozygous for the rare G allele of the first variant had significantly higher postprandial glycaemia and triglycerides and decreased HDL-to-total cholesterol ratio, which are all characteristic features of atherogenic dyslipidaemia and hyperglycaemia, and are together with central obesity the component traits of the MS.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This result for coding variants was replicated in another study in French Caucasians, in which no association was found for four BBS6 coding polymorphisms, including G532V. 12 Furthermore, in the French population two noncoding variants (985 þ 33C4G, À18,597A4T) were found to be significantly more prevalent in obese children compared with control individuals. Children homozygous for the rare G allele of the first variant had significantly higher postprandial glycaemia and triglycerides and decreased HDL-to-total cholesterol ratio, which are all characteristic features of atherogenic dyslipidaemia and hyperglycaemia, and are together with central obesity the component traits of the MS.…”
Section: Discussionmentioning
confidence: 75%
“…It is one of the genes causing BBS, 8,9 where obesity is the prominent clinical feature, and it has therefore been postulated that it might be involved in the pathogenesis of obesity. 11,12 We studied the BBS6 gene in a cohort of Greeks to further investigate its exact role in the development of common obesity. BBS6 gene variants have previously been analysed in two other cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations